Analisis Persepsi Pada Followers Akun @coffeeineseeker Sebagai Sumber Informasi Tentang Coffee Shop - Intan Insanni; Poppy Febriana (LPPM Stikosa - AWS, 2022)
Various types or models of social media platforms will continue to emerge and compete with each other to dominate the market, each social media platform has its advantages and disadvantages. The use of social media has become a natural thing in the life of every individual, the urge to stay abreast of what is trending is one of the reasons why someone uses social media. This study specifically discusses Instagram social media. Instagram is one of the platforms that have more users than young people. Instagram contains a variety of interesting and trendy content in different themes and contexts, easy access to Instagram makes it easy for users to find uploads that suit each individual's interests and preferences. To build an image or personality that you want to show on your Instagram account, one of them is by uploading the interests and preferences of each individual. Interests and likes here are for Coffee Shop enthusiasts who follow the @coffeeineseeker account as a source of the latest information about Coffee Shops. This study was conducted to determine the extent of the influence of the @coffeeseker account in providing information about the Coffee Shop by analyzing the perceptions of the followers of the account. The researcher uses a qualitative descriptive approach with the netnographic method, netnography makes it possible to get the answers needed by listening to the conversations that occur on web pages, analyzing the behavior and opinions of users (Bakry, 2017). The @coffeeineseeker account can be considered as a source of information about Coffee Shops triggered by uploaded photos, captions, and Instagram Stories that disseminate certain Coffee Shop promotions and the latest information about Coffee Shops that will be present or have just started operating.